A dog presenting with syncope due to two different etiologies (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The treatment of syncope depends largely on its possible etiology. Therefore, identifying the cause of syncope is very important in treatment planning. Herein, we report an etiology of syncope caused by pulmonary hypertension (PH) associated with canine filariasis, followed by syncope due to bradyarrhythmia 1 year later. Materials and Methods: An 8-year-old male English Cocker Spaniel was referred to our hospital for a second opinion regarding syncope that the dog had started experiencing approximately 2 months prior. Based on the examination findings, we diagnosed that the fainting was due to heartworm disease and associated PH. After increasing the dose of pimobendan (0.50 mg/kg, q12h), the syncope subsided. However, syncope recurred on the 215th day of the first episode. Results: The findings that differed from those during the initial examination were that cardiac arrest was observed for approximately 5 sec during auscultation, along with sinus arrest. Therefore, to further investigate for syncope, a Holter electrocardiograph was obtained for 3 days. Consequently, sinus arrest was identified as the etiology of the recurrent syncope, and the patient was diagnosed with sick sinus syndrome, Rubenstein classification type II. Following cilostazol (10 mg/kg, q12h) administration, the syncope subsided. Conclusion: This case reports syncope in a dog, which typically occurs due to different etiologies. When a dog has PH, it may be important to think about the possibility of arrhythmias caused by a bigger right heart.J. Adv. Vet. Anim. Res., 9(3): 440–446, September 2022http://doi.org/10.5455/javar.2022.i612